2016
DOI: 10.1002/hipo.22597
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-tethered AKT kinase regulates basal synaptic transmission and early phase LTP expression by modulation of post-synaptic AMPA receptor level

Abstract: The serine/threonine kinase AKT/PKB plays a fundamental role in a wide variety of neuronal functions, including neuronal cell development, axonal growth, and synaptic plasticity. Multiple evidence link AKT signaling pathways to regulation of late phase long-term synaptic plasticity, synaptogenesis, and spinogenesis, as well as long-term memory formation. Nevertheless, the downstream effectors mediating the effects of AKT on early phase long-term potentiation (eLTP) are currently unknown. Here we report that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…To confirm that AZD inhibited AKT activity despite the hyperphosphorylation of AKT, we examined AKT substrates and found significantly decreased phosphorylation levels of both GSK-3β, in a dose-dependent manner, and TSC2 ( Figure 3a,c,d ). Finally, the AKT1/2 inhibitor A6730 (10 mM) was recently found to reduce levels of the AMPA receptor subunit GluA2 ( Pen et al, 2016 ), but we found no reduction even with the highest concentration of AZD or MK ( Figure 3a,d ).…”
Section: Resultsmentioning
confidence: 48%
“…To confirm that AZD inhibited AKT activity despite the hyperphosphorylation of AKT, we examined AKT substrates and found significantly decreased phosphorylation levels of both GSK-3β, in a dose-dependent manner, and TSC2 ( Figure 3a,c,d ). Finally, the AKT1/2 inhibitor A6730 (10 mM) was recently found to reduce levels of the AMPA receptor subunit GluA2 ( Pen et al, 2016 ), but we found no reduction even with the highest concentration of AZD or MK ( Figure 3a,d ).…”
Section: Resultsmentioning
confidence: 48%
“…3a,c). Recently, the AKT1/2 inhibitor A6730 (10 mM) was found to reduce levels of the AMPA receptor subunit GluA2 20 , but we found no reduction even with the highest concentration of AZD or MK (Fig. 3a,d).…”
Section: Resultsmentioning
confidence: 49%
“…4c). Because AKT has been linked to AMPA and NMDA receptor function 20 , we first examined the effect of deleting single Akt isoforms on basal synaptic transmission, presynaptic plasticity and short-term LTP in area CA1. We found normal synaptic input/output curves (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In synaptic tagging, a stimulus establishes molecular "tags" in active synapses that can then become further potentiated in L-LTP by associating with newly synthesized plasticity-related proteins. Kinases triggered during E-LTP are thought to contribute to L-LTP, such as MAPK (Thomas and Huganir, 2004), CaMKII (Ma et al, 2015), protein kinase B (Pen et al, 2016), phosphoinositide 3-kinase (Asrar et al, 2009), and protein kinase C (Jalil et al, 2015).…”
Section: B Subacute Consolidation Of Synaptic Changementioning
confidence: 99%